2012
DOI: 10.1007/s12671-012-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taiji Practice on Mindfulness and Self-Compassion in Healthy Participants—A Randomized Controlled Trial

Abstract: Taiji is regarded as a mind-body practice that is characterized by gentle and mindful body movements. In contrast to the continuously growing evidence base supporting the beneficial effects of Taiji on physical and mental well-being, studies investigating its underlying mechanisms are still scarce. The aim of our study was to examine the impact of Taiji practice on self-attribution of mindfulness and self-compassion, two potential components well known for their health promoting effects. Seventy healthy partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
3
9
1
1
Order By: Relevance
“…In contrast to our findings, two prior studies found that mindfulness significantly increased after Tai Chi intervention (Caldwell et al, 2011; Nedeljkovic et al, 2012). Because these studies included participants of healthy volunteers, mindfulness may not have increased among our participants due to negative modulation from the underlying chronic pain of their OA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, two prior studies found that mindfulness significantly increased after Tai Chi intervention (Caldwell et al, 2011; Nedeljkovic et al, 2012). Because these studies included participants of healthy volunteers, mindfulness may not have increased among our participants due to negative modulation from the underlying chronic pain of their OA.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our sensitivity analysis, which did not find substantial difference between mindfulness change at 12 and 24 weeks, supports the internal validity of our results and that the effects of the error were not complex. While we cannot rule out a lack of power as a confounder of our results, our sample size is similar to those reported from comparable studies (Morone, Greco, & Weiner, 2008; Nedeljkovic et al, 2012). Importantly, the amount of average change in total mindfulness or mindfulness facets from Tai Chi was small (ranged from worsening by 1 point to improving by 1.8 points).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This in turn might build a variety of consequential personal resources (e.g., increased mindfulness, purpose in life, social support), potentially having a strong and lasting impact on participants' daily life [22] . The fact that we have found persistently increased values in selfreported self-compassion, mindfulness and general selfefficacy, as well as decreased values in perceived stress in Taiji course participants two months after course completion [23,24] supports the assumption that long-term effects of a Taiji intervention on participants' daily life might be reported one year after course completion.…”
Section: Journal Of Integrative Medicinesupporting
confidence: 76%
“…Dabei wurde im Vergleich zur Warteliste-Kontrollgruppe (n = 31) in der Taiji-Kursgruppe (n = 28) ein überzufällig höherer Anstieg der Werte für erwartete allgemeine Selbstwirksamkeit und Achtsamkeit - sowohl unmittelbar als auch 2 Monate nach Kursende - beobachtet. Ebenfalls signifikant höher fielen die Anstiegswerte für Self-Compassion der Taiji-Kursabsolventen 2 Monate nach Kursabschluss aus [10,11]. Diese Studienergebnisse weisen auf eine nachhaltig ressourcenaktivierende Wirkung von Taiji bei gesunden, überwiegend erwerbstätigen männlichen und weiblichen Studienteilnehmern hin.…”
Section: Ressourcenaktivierung Durch Taijiunclassified